High-entropy carbide material as well as preparation method and application thereof
Preparation of high-entropy carbide catalysts through rapid Joule thermal shock technology solves the problems of long reaction time and complex process in traditional methods, and achieves efficient and green catalyst preparation and performance improvement, especially in hydrogen precipitation reaction in alkaline electrolytic water Excellent performance.
Patent Information
- Application Number
- CN202411257734.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional methods have problems such as long reaction time, cumbersome process and metal atom aggregation, making it difficult to achieve rapid, efficient and green preparation.
High entropy carbide material is prepared by mixing metal salts, organic carbon sources and pH adjusters in an ethanol solvent, placing them in an oil bath and heating them on a carbon paper carrier.
Fast, simple and green high-entropy carbide catalyst preparation is achieved, which reduces costs and significantly improves catalytic activity, especially the performance of hydrogen precipitation reaction in alkaline electrolytic water.
Smart Images

Figure CN119191298A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a high entropy carbide material and a preparation method and application thereof. Background Art
[0002] Alkaline water electrolysis technology driven by renewable energy is considered to be an effective method for obtaining green hydrogen. However, the kinetics of hydrogen evolution reaction of alkaline catalysts are slow, which increases the energy consumption of the entire system and reduces the economic benefits of the technology. Therefore, it is of great significance to develop efficient and stable preparation technology for alkaline electrocatalysts. Compared with single-element catalysts, binary electrocatalysts can change the ratio of elements to regulate the adsorption free energy of hydrogen intermediates, thereby improving the catalytic activity of hydrogen evolution electrocatalysts. However, due to its compositional limitations and fixed stoichiometric ratio, traditional binary materials are difficult to achieve diversified regulation of hydrogen adsorption free energy, which poses a serious challenge to the development of highly stable and highly active electrocatalysts. Precious metal high-entropy catalysts are catalysts composed of multiple metal elements (five or more). Through the design of diversified components, the electronic interaction of the adsorption energy of reactant intermediates can be conveniently adjusted, thereby improving the activity of the electrocatalyst. Therefore, precious metal high-entropy materials provide new opportunities for obtaining ideal electrochemical hydrogen evolution catalysts.
[0003] High entropy carbides have attracted extensive attention from researchers in recent years due to their high stability and adjustable electronic state. However, although traditional methods, such as the aqueous co-reduction method (patent number: CN202210952748), can prepare high entropy carbide catalysts with good performance and stability, these methods have the challenges of long preparation cycles and harsh environmental conditions. Therefore, it is urgent to develop a new method for preparing high entropy carbide catalysts that is fast, efficient, green and economical. Summary of the invention
[0004] The purpose of the present invention is to provide a high entropy carbide and a preparation method and application thereof, which solves the problems of long reaction time, complicated process and metal atom aggregation of traditional methods by adopting rapid Joule thermal shock technology.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] On the one hand, the present invention provides a high entropy carbide material, the chemical formula of which is (Fe a Co b Ni c Mo d W e Ru f ) xC, wherein a, b, c, d, e, f, and x are stoichiometric ratios, wherein: a=0.04-0.1, b=0.18-0.22, c=0.06-0.1, d=0.23-0.3, e=0.28-0.42, f=0.001-0.09, a+b+c+d+e+f=1, and x=0.6-1.1.
[0007] Another aspect of the present invention provides a method for preparing the above-mentioned high entropy carbide material, the method comprising the following steps:
[0008] S1: Six metal salts of Fe, Co, Ni, W, Mo, and Ru, an organic carbon source, and a pH adjuster are mixed and dissolved in an ethanol solvent, and heated in an oil bath to obtain a viscous sample with a pH of 11 to 13. The viscous sample is added with ethanol until dissolved, and transferred to a carbon paper carrier by drop coating to obtain a high entropy carbide precursor supported on the carbon paper carrier;
[0009] S2: Under vacuum, subjecting the high entropy carbide precursor loaded on the carbon paper carrier obtained in step S1 to Joule thermal shock treatment, and cooling to obtain the high entropy carbide.
[0010] In the above technical solution, further, in step S1, the metal salt is at least one of nitrate, sulfate, and hydrochloride;
[0011] The organic carbon source is at least one of citric acid, glucose, and ethylenediaminetetraacetic acid. Since it contains carboxyl and hydroxyl groups, it can be used as a carbon source and also as a metal ion complexing agent. The ratio of the mass of the organic carbon source to the total mass of the metal is 60% to 110%;
[0012] The pH adjuster is at least one of boric acid, carbonic acid and acetic acid.
[0013] In the above technical solution, further, in step S1, the heating temperature is 60-90° C., and the heating time is 2-6 hours.
[0014] In the above technical solution, further, in step S2, the parameters of the Joule thermal shock treatment are: a heating rate of 10 3 -10 4 ℃ / s, reaction temperature is 800-1300℃, and reaction time is 3-8s.
[0015] The present invention also provides an application of the high entropy carbide material in alkaline electrolyzed water.
[0016] The beneficial effects of the present invention are:
[0017] 1. The present invention adopts rapid Joule thermal shock technology, which takes a short time and solves the problems of long reaction time, complicated process and metal atom aggregation in traditional methods.
[0018] 2. The method of the present invention has simple process, is green and environmentally friendly, and the obtained high entropy carbide catalyst has low cost.
[0019] 3. The present invention successfully prepared Ru-containing high entropy carbides. When the current density was 10 mA cm -2 When the overpotential of hydrogen evolution reaction (HER) is only 13 mV, the performance is greatly improved compared with high entropy carbides without Ru, and it has excellent application potential in alkaline water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is an X-ray diffraction pattern of the high entropy carbide material prepared in Example 1;
[0021] Figure 2 This is the electrocatalytic hydrogen production performance curve of the high entropy carbide material prepared in Example 1. DETAILED DESCRIPTION
[0022] The present invention is described in detail below in conjunction with embodiments, but the present invention is not limited to these embodiments.
[0023] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0024] Comparative Example 1
[0025] A high entropy carbide material (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.23 W 0.42 ) 1.1 The preparation method of C comprises the following steps:
[0026] S1: Five metal salts, FeCl3·6H2O, CoCl2·6H2O, NiCl2·6H2O, WCl6, and MoCl3, were mixed and dissolved in an ethanol solvent at a molar ratio of 0.25:1:0.25:1:1 with 1 g of citric acid and 2 g of boric acid, and heated in an oil bath at 85°C for 5 h to obtain a viscous sample with a pH of 11. The viscous sample was added with ethanol until dissolved, and transferred to a carbon paper support by drop coating to obtain a high entropy carbide precursor supported on a carbon paper support;
[0027] S2: Under vacuum, the high entropy carbide precursor sample loaded on the carbon paper carrier obtained in step S1 is subjected to Joule heat shock treatment in a Joule heat ultrafast heating furnace. The synthesis conditions are: heating rate of 2500°C / s, reaction temperature of 800°C, reaction time of 8s, and the sample is cooled to room temperature to obtain high entropy carbide. The metal content is determined by inductively coupled plasma atomic emission spectroscopy to obtain a chemical formula of (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.23 W 0.42 ) 1.1 High entropy carbides of C.
[0028] Example 1
[0029] A high entropy carbide material (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.23 W 0.41 Ru 0.01 ) 1.1 The preparation method of C comprises the following steps:
[0030] S1: Six metal salts of FeCl3·6H2O, CoCl2·6H2O, NiCl2·6H2O, WCl6, MoCl3, and RuCl3·3H2O were mixed and dissolved in an ethanol solvent with a molar ratio of 0.25:1:0.25:1:1:0.01, and 1 g of citric acid and 2 g of boric acid were heated in an oil bath at 85°C for 5 h to obtain a viscous sample with a pH of 11. Ethanol was added to the viscous sample until it dissolved, and the sample was transferred to a carbon paper support by drop coating to obtain a high entropy carbide precursor supported on the carbon paper support;
[0031] S2: Under vacuum, the high entropy carbide precursor loaded on the carbon paper carrier obtained in step S1 is subjected to Joule heat shock treatment in a Joule heat ultrafast heating furnace. The synthesis conditions are: heating rate of 2500°C / s, reaction temperature of 800°C, reaction time of 8s, and the sample is cooled to room temperature to obtain high entropy carbide. The metal content is determined by inductively coupled plasma atomic emission spectroscopy to obtain a chemical formula of (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.23 W 0.41 Ru 0.01 ) 1.1 High entropy carbides of C.
[0032] The synthesized materials were characterized using XRD techniques, such as Figure 1As shown in the figure, the characteristic peaks presented in the XRD spectrum of both samples correspond to the standard card of single-phase Co6W6C, indicating that the high-entropy carbide is successfully prepared. In addition, compared with the image of undoped Ru element, the characteristic peak of Ru element doping shifts to the right and the sample lattice shrinks, further proving that the high-entropy carbide containing Ru is successfully prepared.
[0033] Example 2
[0034] S1: Six metal salts of FeCl3·6H2O, CoCl2·6H2O, NiCl2·6H2O, WCl6, MoCl3, and RuCl3·3H2O were mixed and dissolved in an ethanol solvent with a molar ratio of 0.25:1:0.25:1:1:0.01, with 0.5 g of citric acid and 1 g of boric acid, and heated in an oil bath at 75°C for 4 h to obtain a viscous sample with a pH of 13. Ethanol was added to the viscous sample until it dissolved, and the sample was transferred to a carbon paper support by drop coating to obtain a high entropy carbide precursor supported on the carbon paper support;
[0035] S2: Under vacuum, the high entropy carbide precursor loaded on the carbon paper carrier obtained in step S2 is subjected to Joule heat shock treatment in a Joule heat ultrafast heating furnace. The synthesis conditions are: heating rate of 2500°C / s, reaction temperature of 800°C, reaction time of 8s, and the sample is cooled to room temperature to obtain high entropy carbide. The metal content is determined by inductively coupled plasma atomic emission spectroscopy to obtain a chemical formula of (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.23 W 0.41 Ru 0.01 ) 0.6 High entropy carbides of C.
[0036] Example 3
[0037] S1: Six metal salts of Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, WCl6, Mn(NO3)2·4H2O, and RuCl3·3H2O were mixed and dissolved in an ethanol solvent with a molar ratio of 0.3:0.9:0.3:1:0.75:0.25, along with 1g of glucose and 2g of acetic acid. The mixture was heated in an oil bath at 60°C for 6h to obtain a viscous sample with a pH of 11. The viscous sample was added with ethanol until dissolved, and the sample was transferred to a carbon paper support by drop coating to obtain a high entropy carbide precursor sample supported on a carbon paper support.
[0038] S2: Under vacuum, the high entropy carbide precursor sample loaded on the carbon paper carrier obtained in step S1 is subjected to Joule heat shock treatment in a Joule heat ultrafast heating furnace. The synthesis conditions are: heating rate of 3000°C / s, reaction temperature of 1300°C, reaction time of 3s, and the sample is cooled to room temperature to obtain high entropy carbide. The metal content is determined by inductively coupled plasma atomic emission spectroscopy. The chemical formula of the high entropy carbide (Fe 0.1 Co 0.18 Ni 0.1 Mo 0.23 W 0.3 Ru 0.09 ) 1.1 C.
[0039] Example 4
[0040] S1: Six metal salts of Fe2(SO4)3, CoSO4, NiSO4·6H2O, WCl6, MoSO4, and RuCl3·3H2O were mixed and dissolved in an ethanol solvent with a molar ratio of 0.25:1:0.5:1.2:0.8:0.05, 1g of ethylenediaminetetraacetic acid and 2g of carbonic acid, and heated in an oil bath at 90°C for 2h to obtain a viscous sample with a pH of 11. Ethanol was added to the viscous sample until it dissolved, and the sample was transferred to a carbon paper support by drop coating to obtain a high entropy carbide precursor sample supported on a carbon paper support;
[0041] S2: Under vacuum, the high entropy carbide precursor sample loaded on the carbon paper carrier obtained in step S1 is subjected to high temperature thermal shock treatment in a Joule heat ultrafast heating furnace. The synthesis conditions are: heating rate of 3000°C / s, reaction temperature of 1000°C, reaction time of 6s, and the sample is cooled to room temperature to obtain high entropy carbide. The metal content is determined by inductively coupled plasma atomic emission spectroscopy to obtain a chemical formula of (Fe 0.06 Co 0.22 Ni 0.1 Mo 0.3 W 0.28 Ru 0.04 ) 1.1 High entropy carbides of C.
[0042] Example 5
[0043] S1: Six metal salts of Fe2(SO4)3, CoNO3, NiNO3, WCl6, MoSO4, and RuCl3·3H2O were mixed and dissolved in an ethanol solvent with a molar ratio of 0.25:1:0.25:1:1:0.01, with 1 g of citric acid and 2 g of boric acid, and heated in an oil bath at 85°C for 3 h to obtain a viscous sample with a pH of 11. Ethanol was added to the viscous sample until it dissolved, and the sample was transferred to a carbon paper support by drop coating to obtain a high entropy carbide precursor sample supported on a carbon paper support;
[0044] S2: Under vacuum, the high entropy carbide precursor sample loaded on the carbon paper carrier obtained in step S1 is subjected to high temperature thermal shock treatment in a Joule heat ultrafast heating furnace. The synthesis conditions are: heating rate of 2000°C / s, reaction temperature of 1200°C, reaction time of 8s, and the sample is cooled to room temperature to obtain high entropy carbide. The metal content is determined by inductively coupled plasma atomic emission spectroscopy to obtain a chemical formula (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.23 W 0.41 Ru 0.01 ) 1.1 High entropy carbides of C.
[0045] Example 6
[0046] Six metal salts of FeCl3·6H2O, CoCl2·6H2O, NiCl2·6H2O, WCl6, MoCl3, and RuCl3·3H2O were mixed and dissolved with 1 g of citric acid and 2 g of boric acid in a molar ratio of 0.25:1:0.25:1:1:0.001 in an ethanol solvent, and heated in an oil bath at 70°C for 5 h to obtain a viscous sample with a pH of 11. Ethanol was added to the viscous sample until it dissolved, and the sample was transferred to a carbon paper support by drop coating to obtain a high entropy carbide precursor sample supported on a carbon paper support.
[0047] Step S2: Under vacuum, the high entropy carbide precursor sample loaded on the carbon paper carrier obtained in step S1 is subjected to high temperature thermal shock treatment in a Joule heat ultrafast heating furnace. The synthesis conditions are: heating rate of 2000°C / s, reaction temperature of 1300°C, reaction time of 8s, and the sample is cooled to room temperature to obtain a high entropy carbide. The metal content is determined by inductively coupled plasma atomic emission spectroscopy to obtain a chemical formula of (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.234 W 0.415 Ru 0.001 ) 1.1 High entropy carbides of C.
[0048] Application Example 1
[0049] The electrocatalytic performance of the high entropy carbide materials prepared in Examples 1-6 and Comparative Example 1 was evaluated using an electrochemical three-electrode system, with the high entropy carbide material as the working electrode, the Hg2Cl2 electrode as the reference electrode, the graphite carbon sheet as the counter electrode, and a 1 M KOH solution as the electrolyte.
[0050] from Figure 2 It can be seen that the high entropy carbide sample of Example 1 has a -2 When the current density is 10 mA cm -2 The HER reaction overpotential is as high as 110 mV. The above experimental results show that compared with the high entropy carbide without Ru, the (Fe 0.04 Co 0.23 Ni 0.06 Mo 0.23 W 0.41 Ru 0.01 ) 1.1 The performance of C samples is greatly improved. Therefore, high-entropy carbide catalysts containing Ru have excellent potential for alkaline water electrolysis.
[0051] The performance test results of Examples 2-6 are shown in Table 1.
[0052] Table 1 Performance test results of Examples 2-6
[0053]
[0054]
[0055] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the above disclosed technical content to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A high entropy carbide material, characterized in that: The chemical formula of the material is (Fe a Co b Ni c Mo d W e Ru f ) x C, wherein a, b, c, d, e, f, and x are stoichiometric ratios, wherein: a=0.04-0.1, b=0.18-0.22, c=0.06-0.1, d=0.23-0.3, e=0.28-0.42, f=0.001-0.09, a+b+c+d+e+f=1, and x=0.6-1.
1.
2. A method for preparing the high entropy carbide material according to claim 1, characterized in that: The method comprises the following steps: S1: Six metal salts of Fe, Co, Ni, W, Mo, and Ru, an organic carbon source, and a pH adjuster are mixed and dissolved in an ethanol solvent, and heated in an oil bath to obtain a viscous sample with a pH of 11 to 13. The viscous sample is added with ethanol until dissolved, and transferred to a carbon paper carrier by drop coating to obtain a high entropy carbide precursor supported on the carbon paper carrier; S2: Under vacuum, subjecting the high entropy carbide precursor loaded on the carbon paper carrier obtained in step S1 to Joule thermal shock treatment, and cooling to obtain the high entropy carbide.
3. The preparation method according to claim 2, characterized in that: In step S1, the metal salt is at least one of nitrate, sulfate, and hydrochloride; The organic carbon source is at least one of citric acid, glucose, and ethylenediaminetetraacetic acid, and the ratio of the mass of the organic carbon source to the total mass of the metal is 60% to 110%; The pH adjuster is at least one of boric acid, carbonic acid and acetic acid.
4. The preparation method according to claim 2, characterized in that: In step S1, the heating temperature is 60-90°C and the heating time is 2-6h.
5. The preparation method according to claim 2, characterized in that: In step S2, the parameters of the Joule thermal shock treatment are: a heating rate of 10 3 -10 4 ℃ / s, reaction temperature is 800-1300℃, and reaction time is 3-8s.
6. Use of the high entropy carbide material according to claim 1 in alkaline electrolysis of water.
